Optimization of gaseous nitriding process parameters for hard surface layer of duplex stainless steel - Maleque, Md. Abdul; Paijan, Lailatul Harina; Othman, Norinsan Kamil; Rahman, Md Mustafizur (Inderscience Publishers, 2018)
The optimization for gaseous nitriding process parameters of duplex stainless steel was performed using Taguchi approach. The nitriding process parameters of temperature, time and gas mixture ratio of NH3 and N2 are considered as input parameters. Three responses are chosen which are surface hardness, wear weight loss and coefficient of friction. The optimum process parameters for surface hardness and coefficient of friction are similar with 550ºC, 16 hour and 0.3 NH3/N2. The study revealed that temperature and time are the most significant factor influencing the responses of nitrided surface of DSS. The formation of hard surface layer contains expanded austenite with thickness layer until 135 µm and maximum hardness of 1440 Hv. The hardness values produced 5 times greater than untreated DSS. The worn surface after wear test has improved with mild wear and smooth abrasion mark.